Analisis Pengaruh Activity Based Costing Terhadap Keunggulan Bersaing dan Kinerja Perguruan Tinggi - Evi Marlina; Siti Samsiah; Hendri Ali Ardi (Akuntansi & Ekonomika, 2018)
This research was conducted in order to know if there is an influence in the use of Activity Based Costing toward competitive advantage and university performance in Pekanbaru. The Activity Based Costing variables were measured by seven indicators, namely top management Support, competition, performance evaluation and compensation, training, non-accounting ownership, resources and consensus and clarity of objective. The competitive advantage variables measuredby five indicators, namely price, quality, delivery dependability, product innovation and time to market. While the university performance variables will be measured by three indicators, research and productivity, employee commitment and industry linkage. The data used in this research was quantitative data, which were data in the numerical scale. The population ofthis research were all university in Pekanbaru. The samples of the research were 39 university in Pekanbaru. Based on the Partial Least Square that used in analyzing the data, the result showed that Activity Based Costing have influence towards competitive advantage, the Activity Based Costing have influence towards university performance, and competitive advantage have not influence towards university performance